'Ziehier het teken van redding: Een touw met een strop': De theologie van W.E.B. Du Bois - Borgman, Erik (Tijdschrift voor theologie, 2017)
W.E.B. Du Bois (1869-1963) is not very well-known in the Low Countries. This article introduces his ideas on religion for a Dutch-speaking audience. In the us the question of Du Bois’ view on religion in general and on black religion in particular, is highly contested. In spite of many seemingly anti-religious statements, Du Bois’ position can be reconstructed as theological by nature. This article does this by focusing mainly on his early masterpiece The Souls of Black Folk (1903). First, it is shown that Du Bois is not just a student of black religion, but that he also understands his mission in life in religious terms, including the historical, sociological and activist aspects. Second, it introduces what Du Bois called the ‘Sorrow Songs’, the songs that enabled blacks to survive the unbearable hardships in their personal and collective lives, as the key to both Du Bois’ writing and to his view on how the world works. Third, the article clarifies that, according to Du Bois, being unhappy and discontent with life as it is, is necessary, and in a certain way unavoidable for blacks in a racist society, which includes discontent with church and religion as they are. With the help of some of the ideas of F. Schleiermacher, this is shown to be not an anti-Christian but a Christian stance. Fourth, the article argues that what has been called ‘divine discontent’ in Du Bois, is neither optimism nor pessimism with regard to the situation of black people, but an expression of ‘a hope not hopeless but unhopeful’, deeper than any despair and stronger than death. It is this hope that has made it possible for black people to survive. It makes them disappear behind what Du Bois analyses as ‘the veil’ of ‘the color line’ that locks them into the categories the white society has available for them, thus making them invisible in what they really are, the saviors of American society. Fifth, the article shows how for Du Bois in the lynching of black people, God is present both in the person lynched - he wrote several stories about a black Christ being lynched - and in the shocked and appalled silence of the black community. In his silence God calls on people to act on his behalf, contributing to a culture in which human nature can come to full expression through the free manifestation of the humanity of all. In closing, the article argues how Du Bois’ position can help us to think theologically in a time of disillusion and despair by considering everything that can be done as a precarious, but real gift of hope not hopeless, but unhopeful.